A deep water Ascidia (Ascidiidae, Tunicata) from the tropical western Pacific - Monniot, F.; Monniot, C. (Zootaxa, 2006)
A single, solitary, free living ascidian, Ascidia alisea sp.nov., collected from a sandy substrate on the Austral Ridge (Polynesia) between 120 and 203 meters depth, is ovoid with a layer of sandy debris adhering to the tunic and has distinctive body muscles and neural area and an unusual course of its vas deferens.